2020
DOI: 10.1589/jpts.32.391
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the deep squat movement and the hip, knee and ankle range of motion and muscle strength

Abstract: We examined and clarified the relationship between the maximum squat depth and the range of motion of the ankle, knee, and hip joints, and the knee and hip muscle strength. [Participants and Methods] Nine healthy males participated in this study and performed a deep squat with the upper extremities raised; the movement was analyzed by two-dimensional motion analysis. We measured the ankle dorsiflexion, hip flexion, and knee flexion ranges of motion, as well as the knee extension and hip flexion muscle strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…That was reason for no correlated with ROM of lower. Yasuhi [34] found that hip flexion, ankle flexion, and knee flexion ROM were highly correlated with the active ROM of the hip, knee and ankle joints during squatting. The present study did not find a significant correlation and this may also be related to the deep squat score being reduced for poor trunk control and excessive forward leaning.…”
Section: Discussionmentioning
confidence: 99%
“…That was reason for no correlated with ROM of lower. Yasuhi [34] found that hip flexion, ankle flexion, and knee flexion ROM were highly correlated with the active ROM of the hip, knee and ankle joints during squatting. The present study did not find a significant correlation and this may also be related to the deep squat score being reduced for poor trunk control and excessive forward leaning.…”
Section: Discussionmentioning
confidence: 99%
“…No es sorprendente que haya habido un creciente interés en el entrenamiento diseñado para evaluar y mejorar el movimiento funcional (Ransdell y Murray, 2016) De esta manera, destacando las compensaciones más relevantes, la rotación externa de los pies puede ser debida a una falta de dorsiflexión de tobillo (Hernández-García y col., 2020). El movimiento adecuado de sentadilla profunda requiere de una gran dorsiflexión del tobillo, flexión de la rodilla, flexión de la cadera y movilidad del tronco (Endo, Miura, y Sakamoto, 2020). Por ello, que la flexión de hombros se pierda, los brazos caigan hacia delante y se produzca una pérdida de disociación lumbo-pélvica podría ser debido a los factores nombrados anteriormente.…”
Section: Discussionunclassified
“…This allows us to know how much of an injury is caused by body imbalance when performing squat movements. For example, the relationship between squat ability and knee ligament injury and hip joint disorder has been [28].…”
Section: Discussionmentioning
confidence: 99%